Board gender diversity, dividend payout, and firm value: study on IDX high dividend 20 - Candy, Candy; Alex, Alex; Marheni, Dewi Khornida (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
The breadth of corporate governance boards encompasses a range of viewpoints and vigilant oversight in assessing management decisions and their impact on dividend strategies. This research seeks to explore how the inclusion of female board directors affects firm value through the dividend payout ratio, drawing on data from companies listed on the IDX High Dividend 20 stock index from 2018 to 2022. Financial and annual reports sourced from the Indonesia Stock Exchange (IDX) and the companies themselves serve as the basis for this investigation. Findings suggest that the involvement of women on boards influences the company's dividend payout ratio. However, there's no observed impact on firm value through this ratio. Interestingly, the presence of women in executive director roles is found to have a noteworthy, direct negative impact on firm value.